BDNF genotype modulates resting functional connectivity in children - Thomason, Moriah E.; Yoo, Daniel J.; Glover, Gary H.; Gotlib, Ian H. (Frontiers in Human Neuroscience, 2009)
A specific polymorphism of the brain-derived neurotrophic factor (BDNF) gene is associated with alterations in brain anatomy and memory; its relevance to the functional connectivity of brain networks, however, is unclear. Given that altered hippocampal function and structure has been found in adults who carry the methionine (met) allele of the BDNF gene and the molecular studies elucidating the role of BDNF in neurogenesis and synapse formation, we examined in the association between BDNF gene variants and neural resting connectivity in children and adolescents. We observed a reduction in hippocampal and parahippocampal to cortical connectivity in met-allele carriers within each of three resting networks: the default-mode, executive, and paralimbic networks. In contrast, we observed increased connectivity to amygdala, insula and striatal regions in met-carriers, within the paralimbic network. Because the BDNF met-allele has been linked to increased susceptibility to neuropsychiatric disorders, this latter finding of greater connectivity in circuits important for emotion processing may indicate a new neural mechanism through which these gene-related psychiatric differences are manifest. Here we show that the BDNF gene, known to regulate synaptic plasticity and connectivity in the brain, affects functional connectivity at the neural systems level. Additionally, we provide the first demonstration that the spatial topography of multiple high-level resting state networks in healthy children and adolescents is similar to that observed in adults.